Forgiveness as a spiritual construct experienced by men serving long-term sentences in Zonderwater, South Africa - Christina Landman; Tanya Pieterse (HTS Teologiese Studies/Theological Studies, 2020)
This article presents the findings of research conducted on ‘forgiveness’ as a spiritual construct, religious survival strategy and meaning-giving tool during incarceration. The research was conducted with 30 men serving long-term sentences in Zonderwater, a correctional centre outside Pretoria, South Africa. A review of literature showed that forgiveness has mainly been seen as something the perpetrator owed the victim and that asking for and granting forgiveness were religious imperatives. However, this study shows that offenders, in the troubled space of incarceration, survived by putting themselves in control of forgiveness. They found peace of mind by granting forgiveness to those who caused them to be incarcerated, whilst at the same time taking responsibility for their own actions. Semi-structured interviews were conducted with the participants. Applying an interpretative phenomenological analysis methodology, the collected data were analysed and the following themes were identified: (1) forgiving those who transgressed against me; (2) the role of politics in forgiveness; (3) God’s role in forgiveness; and (4) the effects of forgiveness on the self.